Comparative assessment of heat tolerance in weevils associated with a fire‐prone ecosystem. (7th December 2022) - Javal, Marion; Terblanche, John S.; Smit, Chantelle; Haran, Julien
Abstract: Fire is an important cause of disturbance which directly shapes many ecosystems worldwide. While the effect of fire on the distribution and regeneration of plant species has been widely documented, little is known on how phytophagous insects are reacting to these disturbances. This study explores the survival strategies of various weevil species, a highly diverse phytophagous beetle group in fire‐prone ecosystems of the biodiversity hotspot of the Cape Floristic Region in South Africa. More specifically, we investigated how the lifestyle of species (location of larval development, phenology of adults, and flight ability) correlates with heat tolerance. We hypothesized that wingless species in particular will show better tolerance to heat as they have a limited ability to escape fire rapidly and usually remain hidden in the soil. The thermal tolerance of a set of sixteen species with divergent lifestyles and geographic distribution was measured using a standard heat knockdown protocol at 48°C. Respirometry was then performed on the most resistant species using a ramping protocol in order to determine CTmax . Our results show that the species tested exhibit high variation in thermal tolerance across taxonomic groups, clustering into three modalities: weak, intermediate, and high tolerance to heat stress. In addition, life history traits (diurnal vs. nocturnal adult activity and location of juvenile stages in plant tissues) likely better explain thermal tolerance at the species level than flight ability or the fire‐proneness of ecosystems. Finally, results revealed that some non‐flying weevil species are highly heat tolerant with CTmax values reaching up to 50.2 and 51.9°C in species among the Ocladiinae and Brachycerinae subfamilies, respectively. Climate change is leading to an increase in the impact and frequency of fires. In this context, this study highlights the diversity of strategies developed by arthropods to escape extreme heat in fire prone ecosystems. Further work is necessary to examine the generality of these patterns across other fire prone ecosystems to better understand behavioural compensation and evolutionary responses, especially given the forecast increases in fire driven by drying and warming associated with climate change. Abstract : The fire prone ecosystems of the cape floristic region host a high diversity of small apterous weevils. It is not known how these low mobility species cope with the extreme temperatures experienced. We carried out a first screening of the heat tolerance of several apterous weevil species in comparison to winged species with contrasting lifestyles. The species form three groups (A, B, and C) without phylogenetic coherence, but whose temperature resistance in adults seems to be linked to the larval lifestyle.